Gambaran State, Trait, Ekspresi Dan Kontrol Marah Pada Individu Emerging Adulthood Yang Melakukan Non-Suicidal Self-Injury - Latumahina, Joy; Dewi, Zahrasari Lukita (MANASA, 2023)
Non-Suicidal Self Injury (NSSI) is self-harming behavior carried out without suicidal thoughts. NSSI behavior can be motivated by expressing unbearable and difficult emotions. One of these emotions is the emotion of anger, which is often associated with aggressive behavior, both towards other people and towards oneself. Spielberger (1988) explained anger from various sides, such as from perspective, which looks at the situation (state), personality traits (trait), expression, and control. This study aims to determine the description of the state, traits, expression, and control of anger in emerging adulthood individuals who commit non-suicidal self-injury. To be specific, this study uses descriptive quantitative methods. In collecting data, this study used the STAXI-2 and NSSI-AT measuring instruments. The data analysis technique used is the descriptive analysis method. The sample criteria for this study were 74 participants aged 18-25 years who carried out NSSI in Indonesia. The study results showed that the NSSI behavior did not describe the full intensity of the anger experienced. Individuals who engage in NSSI have feelings of anger stronger than those expressed physically. Apart from that, individuals who engage in NSSI also tend to suppress their anger and try to calm themselves in a situation that provokes their anger. Based on the result, we recommend that further research includes other variables related to feelings of anger and NSSI.